Kołobrzeg as a city and health resort after the first year of the COVID-19 pandemic - Miedziński, Mariusz (Turystyka i krajoznawstwo, 2021)
The aim of the author was to try to determine the impact of the Covid-19 pandemic on the functioning of the city of Kołobrzeg in terms of the closings and openings of spa treatment and accommodation facilities in the largest Polish spa. Of all Polish health resorts, the city of Kołobrzeg has the largest concentration of tourist accommodation facilities in the country, officially, according to ‘Statistics Poland’ data for 2019, there are 35,363 places in a very attractive location with numerous residential, apartment and hotel investments. As the largest seaside resort, strongly dependent on its tourism and spa functions, it has over the last year struggled with various changes: the functioning of the accommodation base, a significant decrease in budget revenues, an increase in unemployment and at the same time a further intensification of housing, apartment and hotel investments. The course of these processes from February 2020 to March 2021 is an interesting case study showing how large seaside resorts with a leading spa function operated during the Covid-19 pandemic.